Isolation of multidrug-resistant Escherichia coli O157 from goat caecal contents and carcasses in the Somali region of Ethiopia - Dulo, F.; Feleke, A.; Szonyi, Barbara; Fries, R.; Baumann, M.P.O.; Grace, Delia (Addis Ababa University, 2015)
Background: Toxigenic E. coli is an important cause of gastroenteritis in developing countries. In Ethiopia, gastroenteritis due to foodborne disease is a leading cause of death. Yet, there is no surveillance for E. coli O157 and little is known about the carriage of this pathogen in Ethiopia’s livestock. Also, antimicrobial resistance patterns are not well known in this part of the world. Methods: A cross-sectional study was conducted in 2014 to determine the prevalence and antibiotic resistance of E. coli O157 in goat meat, caecal content, and environmental samples collected at a large abattoir in the Somali region of Ethiopia. The samples were enriched in modified tryptone broth containing novobiocin, and plated onto sorbitol MacConkey agar. Isolates were confirmed using indole test and latex agglutination. Antimicrobial susceptibility testing was conducted using the disc diffusion method. Results: A total of 235 samples, including 93 goat carcass swabs, 93 caecal contents, 14 water, 20 hand and 15 knife swabs were collected. Overall, six (2.5%) samples were contaminated with E. coli O157 of which two (2.1%) were isolated from caecal contents, three (3.2%) from carcass swabs and one (7.1%) from water. All isolates were resistant to at least two antibiotics. Two isolates (33.3%) were resistant to over five antimicrobials tested. Abattoir facilities and slaughter technique were conducive to carcass contamination. Conclusions: This study highlights how poor hygiene and slaughter practice can result in contaminated meat, which is especially risky in Ethiopia because of the common practice of eating raw meat. The presence of multidrug-resistant strains of E. coli O157 in goats in a remote pastoralist system may be due to natural resistance and/or transfer of resistance from humans.